1992
DOI: 10.1111/j.1439-0442.1992.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Changes in Cortisol Level, Neutrophil Number and Lyzozyme Activity in Foals during the First 13 Weeks of Life and in their Lactating Mothers

Abstract: Summary In the blood of 11 foals and their lactating mothers (Standardbred) diurnal changes in the cortisol level, neutrophil number and lyzozyme activity were studied during the first 13 weeks of life. The investigations began when a foal reached 7 days of age and were repeated every two weeks till 13 weeks of age. Blood samples were taken from the jugular vein every 4 hours for one day. Experiments were repeated in two following years. In the first year 6 mares and 6 foals born by these mares were examined, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…The results of the present study are consistent with previous reports illustrating the dynamic nature of HPA axis function in the neonatal foal 11–13,24–26 . At birth, basal ACTH and cortisol concentrations were significantly higher than resting concentrations previously reported both in older foals and in adult horses, 27–29 and were similar to cortisol concentrations recently reported in adult horses with colic (13.6 ± 7.6 μg/dL) i . This provides further evidence that the healthy full‐term foal is capable of mounting a cortisol response to periparturient stressors 12,30 .…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study are consistent with previous reports illustrating the dynamic nature of HPA axis function in the neonatal foal 11–13,24–26 . At birth, basal ACTH and cortisol concentrations were significantly higher than resting concentrations previously reported both in older foals and in adult horses, 27–29 and were similar to cortisol concentrations recently reported in adult horses with colic (13.6 ± 7.6 μg/dL) i . This provides further evidence that the healthy full‐term foal is capable of mounting a cortisol response to periparturient stressors 12,30 .…”
Section: Discussionsupporting
confidence: 93%
“…Mares of some warm‐blooded breeds have higher blood leucocyte numbers than stallions (Schalm et al, 1975). Daily (Von Bubna‐Littitz and Jaksch, 1986; Flisinska‐Bojanovska et al, 1992) and circadian fluctuations (Gill et al, 1985) of blood leucocyte counts have also been demonstrated in horses.…”
Section: Introductionmentioning
confidence: 99%
“…Both premature (gestational age o 320 days) and full-term neonatal foals appear to lack a fully mature and responsive HPA axis, as evidenced by blunted cortisol responses to both endogenous and exogenous ACTH, as compared with adult horses. 22,[24][25][26][27][28] In addition, recent studies have identified markedly increased ACTH : cortisol ratios (increased plasma ACTH concentration with correspondingly low serum cortisol concentration) in nonsurviving septic foals as compared with both healthy foals and surviving septic foals. 29,30 Low cortisol concentration in conjunction with increased ACTH concentration suggests that failure of cortisol synthesis is primarily at the level of the adrenal gland, whereas the central portions of the HPA axis appear intact.…”
mentioning
confidence: 99%